Towards more accurate measurement of edge to os distance in low-lying placenta using three dimensional transvaginal ultrasound: an innovative technique - Somayya M. Sadek; Reda A. Ahmad; Hytham Atia; Adel G. Abdullah (BMC, 2018)
Abstract Background Measurement of edge to os distance (EOD) is essential to differentiate low-lying from normal placenta, and to plan for delivery. Till now, measurement by 2D TVS is the gold standard, however, its accuracy is questioned. In this study, we introduced an innovative technique for measurement of EOD using 3D TVS. Our aim was to compare EOD measurements of the standard 2D technique, to those of our innovative 3D technique, and to correlate the difference, if any, with placental site and internal os width. Methods This study was conducted in the ultrasound unit of obstetrics and gynecology department, Zagazig University Hospitals, during the period from June 2014 to August 2017. Seventy six cases in whom the lower placental edge didn't reach the internal os (IO), and the EOD was less than 35 mm, were included in the study. Placental location was identified by 2D transabdominal sonography then 2D TVS was used to measure the EOD in all cases. Our new technique was then applied to measure EOD by 3D TVS following stepwise manipulations of the orthogonal planes in multiplanar view. Width of IO was measured also in all cases. Results The mean EOD measured by 3D TVS was significantly shorter than that measured using the 2D TVS. Anterolateral/posterolateral and lateral placentas were associated with high discrepancy in measurements between both methods, being the highest with lateral group. There was significant positive correlation between the IO width and the degree of difference between the EOD measured by both methods. Conclusions Two dimensional TVS may not be accurate in EOD measurements in many cases of low-lying placentas, and 3D TVS may increase the accuracy of measurements in these cases. This new method is simple, precise and easily applied.